2006
DOI: 10.1111/j.1467-9574.2006.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance assessment and improvement of control charts for statistical batch process monitoring

Abstract: This paper describes the concepts of statistical batch process monitoring and the associated problems. It starts with an introduction to process monitoring in general which is then extended to batch process monitoring. The performance of control charts for batch process monitoring is discussed by means of two performance indices: the overall type I error and the action signal time. Problems associated with the existing approach are discussed and highlighted. Improvements are suggested and checked with the perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Now let us focus on the performance indices of the on-line monitoring system developed for every model (lower part of Table III). The results confirmed that the OTI is closer to the ISL for incoming data when using a leave-one-out strategy in the correction of the limits [11,31] than when this strategy is not used in the correction (the latter result not shown). Nonetheless, the batchwise approach presents a very low OTI value for the D-statistic.…”
Section: Saccharomyces Cerevisiae Cultivationsupporting
confidence: 90%
See 2 more Smart Citations
“…Now let us focus on the performance indices of the on-line monitoring system developed for every model (lower part of Table III). The results confirmed that the OTI is closer to the ISL for incoming data when using a leave-one-out strategy in the correction of the limits [11,31] than when this strategy is not used in the correction (the latter result not shown). Nonetheless, the batchwise approach presents a very low OTI value for the D-statistic.…”
Section: Saccharomyces Cerevisiae Cultivationsupporting
confidence: 90%
“…condition in (iii.5) is satisfied and M 2 is selected, so that at this point the MP model has two phases with one LV. The first phase is divided once again yielding phases [1,31] and [32,44] and then this branch of the recursion is stopped. The second phase is also split up, yielding phases [45, 109] and [110,144].…”
Section: Multi-phase Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…In the monitoring charts, the control limits are initially estimated from theoretical results [17,18] and then adjusted using a leave-one-out approach [13,27] for an imposed significance level (ISL) of 1%. This value is the expected percentage of faults for a batch under NOC.…”
Section: Methodsmentioning
confidence: 99%
“…Typically, two Shewhart control charts based on the Hotelling-T 2 and Squared Prediction Error (SPE) statistics are designed. Their control limits (thresholds) are estimated from normal operating conditions (NOC) process data and later adjusted using cross-validation techniques for an imposed significance level (ISL) [12,13]. Once the scheme is designed, new measurements from a new batch data can be projected onto the data model, yielding to the aforementioned multivariate statistics, to check for the correct performance of the process.…”
Section: Introductionmentioning
confidence: 99%